The Difference of Academic Procrastination between Students Who Are Active and Not Active in Organizations Student Activity Units in the Faculty of Psychology, University of Medan Area - Babby Hasmayni (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to determine the differences in academic procrastination between active and non-active students in student organizations in the Faculty of Psychology, University of Medan Area. The scale of academic procrastination in this study is based on the characteristics of academic procrastination according to Ferrari, Johnson, and McCown. The results shows that There is no difference in academic procrastination between students who are active and not active in participating the organizational activities by looking at the value or coefficient of difference in anava F = 0.200 with P> 0.05. There is significant differences in academic procrastination between male and female students. These results are known by looking at the value or coefficient of difference in anava F = 14.137 with P <0.010. Calculation results from the comparison of empirical mean and hypothetical mean of academic procrastination (112.5 <149.2368), where the empirical mean of academic procrastination is greater than the hypothetical mean, it can be stated that the academic procrastination of students is high.